Computer-aided design of a centrifugal pump - 198700 Sik, Cheng Boon (Sekudai : UTM, 1995)
Hydraulic design of a centrifugal pump is an indirect problem where the unknown variables are more than the equations available. To solve this type of problem, some of the unknown parameters need to be assumed. Then by trial and error and iterating process, the solution can be obtained. This process if done manually will consume a lot of time and is a laborious task. This type of process is best done by the compuer. So a program is developed to solve the hydraulic design problem. The primary objective of this project is to develop a software for the hydraulic design of a centrifugal pump. This program covers the design of the impeler inlet and outlet, design of the vane course by suing the polar coordinate method and the involute casing design. users have to key in three data (discharge, rotational speed and the head) and the rest of the hydraulic design work will be done by the program. This types of impeller that canbe designed by this program are radial flow impellerof lof low specific speed (ranging from 30-90) and the Francis-type impeller of medium specific speed (ranging from90-150). The programming language used for this program is C language and operate in Dos environment.